EXPLOITATION AND DISADVANTAGE. (1st December 2015) - Ferguson, Benjamin
Abstract: According to some accounts of exploitation, most notably Ruth Sample's (2003 ) degradation-based account and Robert Goodin's (1987 ) vulnerability-based account, exploitation occurs when an advantaged party fails to constrain their advantage in light of another's disadvantage, regardless of the cause of this disadvantage. Because the duty of constraint in these accounts does not depend on the cause of the disadvantage, the advantaged's duty of constraint is what I call a 'come-what-may' duty. I show that come-what-may duties create moral hazards that can themselves be exploited by the disadvantaged parties. In such cases these accounts of exploitation are either self-frustrating or over-demanding.